2009
DOI: 10.1007/s00774-009-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulates bone metabolism-associated gene expression in osteoblast cells

Abstract: Smoking has a broad range of physiological effects, such as being a risk factor in osteoporosis, bone fracture incidence, and increased nonunion rates. Recent studies showed that nicotine has effects at the cellular level in human osteoblast cells. To identify possible mechanisms underlying nicotine-induced changes in osteogenic metabolism, we defined changes in proliferation and osteocalcin, type I collagen, and alkaline phosphatase gene expression after treating human osteosarcoma cells (MG63), with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 21 publications
10
96
1
1
Order By: Relevance
“…(41,42) Nicotine, a major ingredient in tobacco, has been reported to induce both stimulation and inhibition of proliferation and differentiation of osteoblasts. (43) Rothern and colleagues (44) demonstrated in a cultured human osteoblast-like cell line that nicotine, in low concentrations, increases cell proliferation and expression of genes that mediate bone formation. High concentrations of nicotine were shown to suppress osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
“…(41,42) Nicotine, a major ingredient in tobacco, has been reported to induce both stimulation and inhibition of proliferation and differentiation of osteoblasts. (43) Rothern and colleagues (44) demonstrated in a cultured human osteoblast-like cell line that nicotine, in low concentrations, increases cell proliferation and expression of genes that mediate bone formation. High concentrations of nicotine were shown to suppress osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a less clear image emerges from other studies, indicating no positive reduction in OA associated with smoking (Wilder et al, 2003). Because it was shown that nicotine exerts both positive and negative modulatory effects as a function of its concentration (Rothem et al, 2009), differences in conclusions from the various studies might depend upon the amount of circulating nicotine in the patient's blood.…”
Section: G A7 Nicotinic Acetylcholine Receptors and The Immune Connementioning
confidence: 97%
“…Low levels of nicotine upregulate osteocalcin, type I collagen and alkaline phosphatase gene expression. 22 In human osteoblasts, nicotine induces an increase in tumor necrosis factor-a secretion leading to reduced bone formation by osteoblasts and increased osteoclastic resorption. tumor necrosis factor-a has particularly potent effect on osteoclastogenesis, as it not only promotes RANKL production but synergizes with RANKL to amplify osteoclastogenesis.…”
Section: Direct Effects On Bone Cellsmentioning
confidence: 99%